PENGARUH SUKU BUNGA BI DAN NILAI TUKAR RUPIAH TERHADAP RETURN SAHAM PT TELEKOMUNIKASI INDONESIA TBK - Dewangga Kreshnadjati; Nursito Nursito (FKIP, Universitas Banten Jaya, 2022)
This study aims to examine the effect of BI interest rates and rupiah exchange rates on stock returns of Indonesian telecommunications companies. This research is included in quantitative research. This study obtained data from Bank Negara Indonesia for the 2015-2019 period and from the share value of PT Telekomunikasi Indonesia Tbk for the 2015-2019 period. The research method used in this study is multiple linear regression, T test and F test. The independent variables in this study are the BI interest rate and the rupiah exchange rate, while the dependent variable is stock returns. The results of this study indicate that the BI interest rate and the rupiah exchange rate have no effect on the stock return of PT Telekomunikasi Indonesia Tbk for the 2015-2019 period either partially or simultaneously.